(untitled) (Educação e Pesquisa, 2015)
This text focuses on two driving ideas: educational assessment and quality of education. Sometimes the relationship between these two ideas is linearly considered, as if assessment per se could improve the quality of education. This text analyzes a hegemonic position in our society – according to which assessment, under the logic of control, has directed an education that claims to have high quality – and unveils the consequences of this logic of assessment for the school, the curriculum and teacher education. In contraposition, from a democratic and emancipatory perspective, it presents and defends a counter-hegemonic reference for the quality of education, realized in Paulo Freire’s policy, theory and practice as the Secretary of Education of São Paulo city, from 1989 to 1992. In this period, the educational policy proposed was the construction of a public, popular, and democratic education. For Freire (1997, p. 116): “[...] the question that we face is to fight for the understanding and the practice of assessment as an instrument of appraisal of ‘what to do’ of subjects who are critical and thus at service of liberation, not of taming”II.